(untitled) (International journal of artificial intelligence, 2026)
This article provides a comprehensive scientific analysis of the influence of employee motivation systems on labor productivity within hotel enterprises. In the context of intensifying competition in the global hospitality industry, effective human resource management has emerged as a critical determinant of service quality and organizational performance. The study examines key theoretical frameworks of motivation, including intrinsic and extrinsic motivational factors, and evaluates their practical application in hotel management. Special attention is devoted to financial incentive schemes, non-monetary motivation tools, career development opportunities, and organizational culture as drivers of employee productivity. The article also explores international best practices and highlights implications for hotel enterprises in Uzbekistan seeking to improve workforce efficiency and service delivery standards.